Effectivity of Telemonitoring Toward Quality of Life in Patients with Chronic Obstructive Pulmonary Disease (COPD): A Systematic Review and Meta-Analysis - Vidya, Ananda Pipphali; Jayadi, Jansen; Utama, Karen Elliora; Ren, Kenneth; Wirawan, Aditya; Nugroho, Nyityasmono Tri (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Chronic obstructive pulmonary disorder (COPD) is the third-leading cause of death worldwide. COPD treatment is essential to manage and attenuate the progression of symptoms. Home-based telemonitoring interventions showed several promises in increasing COPD patients' quality of life (QoL) and outcomes. However, various results were obtained in recent studies, making a secondary research presence needed to establish clear risks and benefits. This study aimed to analyze the effect of telemonitoring on QoL among COPD patients. Methods: This study used the Preferred Reporting Items of Systematic Review and Meta-Analysis (PRISMA) reporting guidelines on several databases from February until April 2023. We performed screening and selection, followed by data extraction and quantitative analysis with Review Manager 5.4 Software. The risk of bias assessment was performed using the RoB 2.0 Cochrane tool. Results: Ten randomized controlled trials (RCTs), mostly low-risk of bias, were included. We found a reduction in Saint George's Respiratory Questionnaire (SGRQ) score (mean difference (MD) -1.13 [95% CI -4.23, 1.97; p = 0.47]) and Hospital Anxiety and Depression Scale (HADS) for anxiety (MD-0.16 [95% Cl -0.96, 0.63; p = 0.69]). There was no significant effect of HADS on depression and EuroQol-5 Dimension (EQ-5D). Conclusion: This study suggests that telemonitoring improves QoL in COPD patients, especially for SGRQ and HADS anxiety scores. We suggest a larger number of studies to evaluate the effect of telemonitoring on depression and anxiety. We also encourage the integration of telemedicine with the present care system to achieve the best beneficial outcome for patients.